ANALYSING RELATIONSHIP MARKETING TACTICS AT PT. BANK SULUTGO SIAU - Ateng, Hana Febrina; Worang, Frederik G; Tumiwa, Johan (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Since more competition in business nowadays, many companies are required to build long-term profitable relationship with customers and to achieve customer loyalty. All of company and from every industry tried giving their best to maintained customers satisfaction. One type of services companies that important in the business world are banks that has work as a financial institution and financial intermediary for everyone. There are so many ways and differences relationship marketing tactics implemented for the customers. This study analyses the relationship of marketing tactics namely service quality, communication and price perception in PT. Bank SulutGo Siau. Used qualitative method, 10 customer were interviewed to collect the data. A semi-structure interview is used in this research to collect primary data. Result and conclusion showed that service quality, communication and price perception as became indicators in this result has positive responses from customers Bank SulutGo Siau.Â Keywords: relationship marketing tactics, service quality, value offers, communication.